2021
DOI: 10.21826/2446-82312021v76e2021001
|View full text |Cite
|
Sign up to set email alerts
|

Riqueza e fitossociologia de plantas vasculares em dunas costeiras de Torres, Rio Grande do Sul, Brasil

Abstract: RESUMO-Os aspectos geomorfológicos e climáticos influem no mosaico de ambientes existentes na região norte do Rio Grande do Sul, do qual destacam-se as dunas costeiras. O objetivo deste estudo foi realizar o levantamento florístico, através de caminhamento, e caracterizar a estrutura vegetacional por meio da avaliação de parâmetros fitossociológicos em 45 parcelas, de uma porção de dunas costeiras, Torres, RS. Foram identificadas 141 espécies, 104 nativas e 37 exóticas, distribuídas em 54 famílias. As famílias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We obtained 232 occurrence records of P. asperius from online platforms. Data collected by scientific literature review identified eight occurrence records of the species in the municipalities of Osório (Boldrini et al 2008), Pelotas (Venzke et al 2018), Porto Alegre (Brack et al 1998) Rio Grande (Costa et al 2003;Kafer et al 2011), Tapes, Palmares do Sul (Becker et al 2007) and Torres (Dewes et al 2021). Thirty occurrences of P. asperius were record by our field expeditions, from which samples were collected and taken to the herbarium for future studies (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…We obtained 232 occurrence records of P. asperius from online platforms. Data collected by scientific literature review identified eight occurrence records of the species in the municipalities of Osório (Boldrini et al 2008), Pelotas (Venzke et al 2018), Porto Alegre (Brack et al 1998) Rio Grande (Costa et al 2003;Kafer et al 2011), Tapes, Palmares do Sul (Becker et al 2007) and Torres (Dewes et al 2021). Thirty occurrences of P. asperius were record by our field expeditions, from which samples were collected and taken to the herbarium for future studies (Tab.…”
Section: Resultsmentioning
confidence: 99%